Studying Abroad as a Means of Preparing Future Music Teachers in China - Wang, Ziwen (Educational Challenges, 2024)
The concept of studying abroad as a means of preparing future music teachers in China has a rich and complex history, reflecting the nation’s evolving educational philosophies, political changes, and cultural exchanges. The purpose of this study is to present the genesis of using studying abroad as part of the professional training for future music teachers, detailing the goals and social mandates across various stages of Chinese state development. The article also draws attention to the organic "embeddedness" of such a means of training future music teachers in the Chinese system of professional and higher music-pedagogical education, especially of vocal practices that are not traditional for Chinese culture. Methodology. The study employs a historical-analytical approach, examining primary and secondary sources to trace the evolution of studying abroad as a practice for Chinese music educators. This includes an analysis of normative documents and policy papers available on official educational authority and institution websites. Additionally, qualitative data from interviews with contemporary music educators who have studied abroad provide insights into current practices and perceptions. The findings reveal that the practice of studying abroad for music education, primarily for personal music career development and secondarily for teaching, has been prevalent throughout Chinese history, and has undergone significant transformations over the past century. In the modern period, China continues to send a significant number of students abroad, supported by initiatives such as the China Scholarship Council and ‘One Belt – One Road’ Initiative. These programs facilitate grant support and promote cultural exchange and international cooperation, enriching the professional development of future music teachers in China. The study concludes that international educational experiences have profoundly impacted Chinese music education. Educators trained abroad have introduced diverse musical styles, innovative teaching methodologies, and a global perspective that enhance the learning experience of Chinese students. The integration of international practices has elevated the standards of music education in China, and gained global recognition. However, challenges remain in balancing traditional Chinese music with Western influences, and ensuring equitable access to international education opportunities. The study highlights the need for continuous adaptation and the development of strategies to address these challenges, ensuring that the benefits of studying abroad are fully realised in the Chinese educational context.